Biomimetic Mesoporous Cobalt Ferrite/Carbon Nanoflake Helices for Freestanding Lithium‐Ion Battery Anodes. Issue 27 (17th July 2020) - Thi Thanh Dang, Nhan; Nguyen, Thanh‐Dinh; Lizundia, Erlantz; Quoc Le, Thang; MacLachlan, Mark J.
Abstract: Structural biomimicry is a fascinating concept to explore hierarchically organized nanomaterials for mechanical structures, catalysis, sensing, and energy storage applications. Here we report the fabrication of biomimetic mesoporous cobalt ferrite/carbon nanoflake materials with helical morphologies and evaluate their electrochemical properties as free‐standing lithium‐ion battery (LIB) anodes. Iridescent chiral nematic mesoporous chitosan films obtained from crab shells were combined with binary metallic ions to afford helical cobalt ferrite/chitosan membranes. The cobalt ferrite/chitosan composites were thermally converted to cobalt ferrite/carbon replicas with hybrid nanoflakes arranged in a twisted Bouligand‐type mesoporous network. The structure of the materials was probed by electron microscopy, powder X‐ray diffraction, and Raman spectroscopy. We directly used these freestanding cobalt ferrite/carbon films as binder‐ and additive‐free LIB anodes, where they showed a first discharge capacity of 862 mAh g −1 (at 100 mA g −1 ), which faded during subsequent charge‐discharge cycles. Our work demonstrates a new potential use of chiroptical chitosan membranes to develop energy storage materials, a process that may be extended to other metal‐oxide based components. Abstract : A chitin membrane extracted from crab shells was chemically transformed into an iridescent, photonic chitosan membrane with a chiral structure. This membrane was used as a template to construct cobalt ferrite/chitosan nanocomposite materials. Upon pyrolysis, mesoporous cobalt ferrite/carbon composites were obtained. These materials could be used as free‐standing electrodes without a binder or other additives, and were evaluated for use in lithium ion batteries. The materials show good resistance to cracking during charge/discharge cycling.